2006
DOI: 10.3892/ijo.29.6.1601
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of peroxisome proliferator-activated receptor γ1 splice variants in human colorectal cell lines

Abstract: Abstract. Peroxisome proliferator-activated receptor Á (PPARÁ) is a member of the nuclear hormone receptor family. In colon, this transcription factor is involved in differentiation of absorptive cells. PPARÁ participates also in colon carcinogenesis and cancer progression. Two isoforms, namely PPARÁ1 and PPARÁ2, have been described. Recently, new PPARÁ1 transcripts whose translation raises PPARÁ1 protein have been characterised. They differ from each other by combination of untranslated exons localised in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
(58 reference statements)
1
4
0
Order By: Relevance
“…These studies indicate that glutamine has different regulatory effects on PPARγ levels in different intestinal cell types. In our study, the expression levels of PPAR‐γ decreased significantly after the fish were fed different concentrations of Gln, which was in line with the results of the previous study on human colorectal Caco‐2 cells (Fiatte et al, ). The molecular mechanism of the inhibitory effect of Gln on PPAR‐γ expression in fish needs further study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These studies indicate that glutamine has different regulatory effects on PPARγ levels in different intestinal cell types. In our study, the expression levels of PPAR‐γ decreased significantly after the fish were fed different concentrations of Gln, which was in line with the results of the previous study on human colorectal Caco‐2 cells (Fiatte et al, ). The molecular mechanism of the inhibitory effect of Gln on PPAR‐γ expression in fish needs further study.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies have shown that glutamine can enhance the transcriptional activity of PPAR‐γ in a dose‐ and time‐dependent manner in the intestinal epithelial cell line IEC‐6 by stimulating the PPAR‐γ ligands 15‐HETE and 13‐OXO‐ODE (Ban, Sprunt, Martin, Yang, & Kozar, ). However, in human colorectal Caco‐2 cells, Fiatte et al, () reported that PPAR‐γ expression levels were decreased by medium supplementation with l ‐glutamine. These studies indicate that glutamine has different regulatory effects on PPARγ levels in different intestinal cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Like HNF4a, many members of the nuclear receptor superfamily also express multiple variants. Peroxisome proliferator-activated receptor (PPAR) is encoded by 3 different gene loci (PPARA, PPARD, and PPARG), each generating multiple alternatively spliced isoforms to give rise to further 2, 3, and 2 different polypeptides, respectively, that differ at either N or C termini (Chen et al, 2006;Fiatte et al, 2006). Truncation mutants such as PPARd2 (Lundell et al, 2007) and PPARgD5 have been found to act as dominant-negative forms of the nuclear receptor, where PPARgD5 plays an important role in negative feedback to alter Peroxisome proliferator-activated receptor gamma (PPARg)dependent transcription activity and adipocyte differentiation in obesity (Aprile et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Rare mutations have been reported and more recently dominant negative variants of the receptor were identified although the biological impact remains to be established firmly [179]. Similarly, altered isoforms may be overexpressed in cancer [180183]. Cytogenetic rearrangement has been identified in follicular thyroid cancer fusing the PAX-8 transcription factor to PPAR γ .…”
Section: Pparγ Signaling In Cancermentioning
confidence: 99%